Capital Flows and Financial Stability : Monetary Policy and Macroprudential Responses - Unsal, Filiz (Washington, D.C. : International Monetary Fund, 2011)
The resumption of capital flows to emerging market economies since mid 2009 has posed two sets of interrelated challenges for policymakers: (i) to prevent capital flows from exacerbating overheating pressures and consequent inflation, and (ii) to minimize the risk that prolonged periods of easy financing conditions will undermine financial stability. While conventional monetary policy maintains its role in counteracting the former, there are doubts that it is sufficient to guard against the risks of financial instability. In this context, there have been increased calls for the development of macroprudential measures, with an explicit focus on systemwide financial risks. Against this background, this paper analyses the interplay between monetary policy and macroprudential regulations in an open economy DSGE model with nominal and real frictions. The key result is that macroprudential measures can usefully complement monetary policy. Even under the "optimal policy," which calls for a rather aggressive monetary policy reaction to inflation, introducing macroprudential measures is found to be welfare improving. Broad macroprudential measures are shown to be more effective than those that discriminate against foreign liabilities (prudential capital controls). However, these measures are not a substitute for an appropriate moneraty policy reaction. Moreover, macroprudential measures are less useful in helping economic stability under a technology shock.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet